Model villages: A pathway towards inclusive development - BHATTACHARYYA, SANGEETA; BURMAN, R ROY; PADARIA, R N; SHARMA, J P; PAUL, SUDIPTA; ROY, PINAKI (The Indian Journal of Agricultural Sciences, 2021)
Model Villages can serve as miniature self-sufficient, sustainable and equitable units. One village can inspire other villages and if in this way, the developmental efforts cover whole of rural India, then India can set example of inclusive development in global charts. Not only food and nutritional security through scientific farming but also sustainable ecological balance, enhanced income and equitable distribution, modern infrastructure and along with social harmony and brotherhood can serve as a milestone in the pathway of achieving inclusive development and an Atmanirbhar Bharat. Extension professionals of State Departments and Frontline system of ICAR can work towards developing these sustainable micro-units and then replicating them at district and State levels. The 5 domains and their sub-domains should remain the crux of formulating Model Village Development Programs.